Preferences for COVID-19 vaccination information and location: Associations with vaccine hesitancy, race and ethnicity. Issue 45 (29th October 2021) - Fisher, Kimberly A.; Nguyen, Ngoc; Crawford, Sybil; Fouayzi, Hassan; Singh, Sonal; Mazor, Kathleen M.
Highlights: Preferences for being informed of and receiving the COVID-19 vaccine vary by vaccine hesitancy and race. COVID-19 vaccine hesitant individuals prefer to be informed via a conversation with their doctor. Individuals who are not sure whether to be vaccinated prefer to be vaccinated at a doctor's office. Black race was associated with preferring to be vaccinated at a doctor's office. Healthcare provider involvement in COVID-19 vaccination efforts may increase vaccine uptake. Abstract: This study examined the association between preferences for being informed about the COVID-19 vaccine and where to receive it with vaccination intent and race/ethnicity. We conducted an online survey, oversampling Black and Latino panel members. The 1668 participants were 53.2% female, 34.8% White, 33.3% Black, and 31.8% Latino. Participants who were vaccine hesitant (answered "not sure" or "no" to vaccination intent) were more likely to prefer a conversation with their doctor compared to those who answered "yes" (25.0% and 23.4% vs 7.8%, P  < .001, respectively). Among participants who responded "not sure", 61.8% prefer to be vaccinated at a doctor's office, compared with 35.2% of those who responded "yes" ( P  < .001). Preferred location differed by race/ethnicity ( P  < .001) with 67.6% of Black "not sure" participants preferring a doctor's office compared to 60.2% of Latino and 54.9% of White "not sure" participants. These findings underscore the need to integrate healthcare providers into COVID-19 vaccination programs.